TINJAUAN KEMAMPUAN BIOMOTORIK ATLET KARATE DOJO KANTOR PU (PEKERJAAN UMUM) KOTA SOLOK - SATRIA VALIANTIANUS; Endang Sepdanius; Septri Septri (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The problem in this study is that it originated from the achievements of the Solok City Public Works (PU) office dojo karate athlete. The purpose of this study was to determine the biomotoric ability of the Dojo office Public Works (Solok) karate athlete. This type of research is descriptive. The population in this study amounted to 25 athletes. The sampling technique uses purposive sampling. The sample in this study amounted to 21 male athletes. Data collection techniques with: 1) Bleeep test is an aerobic endurance test, 2) Leg dynamometer is a test of leg muscle strength, 3. Standing broad jump is a test of the explosive strength of leg muscles, 4) Two hand medicine ball put is a test of arm muscle explosive power , 5) Nelson hand reaction test is a hand reaction speed test, 6) Sit and reach is a flexibility test, 7) Shuttle run is an agility test, 8) Stork stand is a balance test, 9) Ballwerfen und-fangen is an eye-hand coordination test . Data were analyzed using descriptive statistics. The results were obtained as follows: 1) Aerobic endurance (Vo2max) athletes included in the middle classification, 2) limb muscle strength included in the middle classification, 3) explosive muscle leg power included in the classification is less, 4) explosive power of the athlete's arm including in the classification is lacking, 5) The speed of the reaction of the athlete's hand is included in the middle classification, 6) The athletes 'included in the classification is sufficient, 7) The agility of the athletes is included in the middle classification, 8) The balance of the athletes is classified as lacking, 9) The coordination of athletes' eyes includes in the middle classification.